Authority of Tegallalang Customary Village Utilizing Community Participation in Managing Ceking Tourist Attractions, Tegallalang District, Gianyar Regency - I Gede Parwata; Nyoman Diah Utari Dewi; Ida Ayu Putu Sri Widnyani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The management of the rice terrace tourist attraction in Ceking, Tegallalang District, Gianyar, presents a unique tourism model due to its location between two villages. The terraces are situated in Kedisan Village, while the best viewpoints are in Tegallalang Village. This research aims to analyze the authority of the Tegallalang Traditional Village in utilizing community participation for managing the Ceking tourist attraction and to develop a suitablemanagement model for community empowerment. The study employs a qualitative approach with case study methods, including data collection through in-depth interviews, field observations, and document analysis. The findings reveal that the Tegallalang Traditional Village's authority in managing the tourist attraction is not fully optimized due to limited community involvement. Moreover, while the attraction is popular among tourists, thefacilities need improvement. The proposed management model emphasizes integration among traditional villages, Subak, government, tourism actors, and the Kedisan Village community, aiming to empower local communities through collaborative management.